A Photoredox Coupling Reaction of Benzylboronic Esters and Carbonyl Compounds in Batch and Flow. - Chen, Yiding; May, Oliver; Blakemore, David C; Ley, Steven V (American Chemical Society (ACS), 2019)
Mild cross-coupling reaction between benzylboronic esters with carbonyl compounds and some imines was achieved under visible-light-induced iridium-catalyzed photoredox conditions. Functional group tolerance was demonstrated by 51 examples, including 13 heterocyclic compounds. Gram-scale reaction was realized through the use of computer-controlled continuous flow photoreactors.
Keywords: 3402 Inorganic Chemistry; 3405 Organic Chemistry; 34 Chemical Sciences